Integrasi Norma Dan Nilai Budaya Dalam Upaya Mewujudkan Desa Bersih Melalui Komunikasi Islam - Rudi Salam; Sahrul; Mailin (STAI Bumi Silampari, 2025)
This research aims to find out how the integration of cultural norms and values in an effort to realize a clean village through Islamic communication. This research uses a descriptive qualitative approach with field research method to deeply understand the phenomenon of the Clean Village tradition in East Halongonan Sub-district. The results showed that the Clean Village Tradition in East Halongonan Sub-district contains various norms and values that reflect the acculturation of culture, religion, and local philosophy. The norms include social norms in the form of the spirit of mutual cooperation and collective participation regardless of social status; customary norms that regulate ritual procedures from generation to generation such as the preparation of offerings and customary deliberations; and religious norms that emphasize the implementation of joint prayers and recitations according to Islamic teachings. Meanwhile, the values reflected in this tradition include the value of togetherness and mutual cooperation as a form of solidarity, the value of gratitude and respect for ancestors as a form of spirituality and cultural preservation, the value of social responsibility that invites all residents to maintain village harmony, and the value of deliberation that reflects democratic decision-making. All of these norms and values are in line with the philosophy of Poda Na Lima, making this tradition not only a cultural heritage, but also a means of shaping the social and spiritual character of the community.